Kazakh music in the global context - KAZTUGANOVA, A.; OMAROVA, A.; KASIMOVA, Z.; TURMAGAMBETOVA, B.; KUZEMBAY, S. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT The relevance of the chosen theme is determined by the presence of the "national code" as the basis of authentic traditional music, its modernization while maintaining the original identity. The main purpose of the article is to study the new forms of creative activity of musicians, scientific, theoretical and pragmatic aspects of the musical language. The methodology of research is based on the principles of historical, cognitive, and comparative analysis. The data that was obtained can be used in the educational process at lectures in the following disciplines: "Kazakh music History", "National musical culture", "Folk musical creativity," etc.RESUMEN La relevancia del tema elegido está determinada por la presencia del "código nacional" como base de la música auténtica tradicional y su modernización manteniendo la identidad original. El objetivo principal del artículo es estudiar las nuevas formas de actividad creativa de los músicos y los aspectos científicos, teóricos y pragmáticos del lenguaje musical. La metodología de investigación se basa en los principios del análisis histórico, cognitivo y comparativo. Los datos obtenidos se pueden utilizar en el proceso educativo en conferencias en las siguientes disciplinas: "Historia de la música kazaja", "Cultura musical nacional", "Creatividad musical popular".